Assessment of Quality of life in Caregivers of Patients with Mental Disorder in Fatemie hospitals of Semnan city - Keighobadi, Sifollah; Neishabouri, Masomeh; Haghighi, Neda; Sadeghi, Tahereh (Advances in Nursing & Midwifery, 2013)
Abstract Background : Families of patients with mental disorder endure remarkable hardship for coping with psychiatry symptom and they confront physical and emotional stresses. Maintaining and improving the quality of life is an important task for nurses. This study was designed to Determination of Quality of life in Caregivers of Patients with mental disorder in Fatemie hospitals of Semnan university of Medical Sciences. Method : A descriptive design was used. Samples consisted of Caregivers of Patients with mental disorder (Schizophrenia, Mania, Major Depressuon( took part in this study. Data were gathered by questionnaire (Quality of life family version) in domains: physical, psychological, social and spiritual. Validity through content validity and reliability with a Cronbach's Alpha / was approved. Data were analyzed using SPSS software. Results : Most Caregivers of Patients with mental disorder are Female ( ) with a mean age of years and patient's wife ( ). The results of study showed that, majority of caregivers record at in physical ( . ), psychological ( ), social ( ) and in spiritual ( . ) as partly desirable level and the QOL scores of caregivers was . from . There was a significant association between quality of life and duration of caregiving (p = / ). Conclusion : copping with disease crisis and explore reasonable about further is more important. Nurses necessary to understand the necessity of family to support and give information. This issue improves Health and Well-being in families. Key words : Quality of life, caregivers, mental illness, Schizophrenia, Mania, Major Depressuon.